Assessing the relation of USDA conservation expenditures to suspended sediment reductions in an Iowa watershed. (15th September 2016) - Villarini, Gabriele; Schilling, Keith E.; Jones, Christopher S.
Abstract: From 1936 to 2010, U.S. Department of Agriculture (USDA) agencies spent 293.7 billion (value adjusted for inflation at the 2009 level) on conservation programs. Of these expenditures, 75.2 billion (26%) were allocated for technical assistance (TA; it is related to costs associated with USDA field staff providing their expert advice to farmers) and 218.5 billion (74%) for financial assistance (FA; monetary incentives for farmers to adopt conservation programs). A major environmental goal of these programs was to reduce soil erosion and sediment leaving the land. In this study, we correlate expenditures on FA and TA programs to a unique long (1937–2009) record of total suspended solids (TSS) and sediment load (SL) for the Raccoon River at Van Meter, Iowa. Study results suggest that three predictors (rainfall, TA and FA) are important in explaining the temporal changes in annual TSS and SL and provide evidence that USDA expenditures helped reduce TSS and SL in the Raccoon River. TA was more effective than FA in reducing TSS levels in the watershed. Our empirical model represents an initial, broad-scale attempt to correlate conservation expenditures to a specific water quality outcome, although more work is needed to disentangle the impacts associated with other unexplored factors. Highlights: We examine the role played by expenditures by USDA agencies in reducing soil erosion. Out of the money spent, 26% (74%) was allocated for technical (financial) assistance. We examine the efficacy of these programs for the Raccoon River at Van Meter, Iowa. Reductions in suspended sediment leaving the land are linked to these USDA programs. Technical assistance has been more effective in reducing soil erosion.